2020
DOI: 10.7249/rra323-1
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for Assessing Models of the COVID-19 Pandemic to Inform Policymaking in Virginia

Abstract: Limited Print and Electronic Distribution RightsThis document and trademark(s) contained herein are protected by law. This representation of RAND intellectual property is provided for noncommercial use only. Unauthorized posting of this publication online is prohibited. Permission is given to duplicate this document for personal use only, as long as it is unaltered and complete. Permission is required from RAND to reproduce, or reuse in another form, any of its research documents for commercial use. For inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Secondly, the deep transfer learning (DTL) model [ 61 ] focuses on real-time remote surveillance and monitoring of mask-wearing protocols at points of interest. Thirdly, the University of Virginia Biocomplexity Center PatchSim COVID-19 [ 62 ] hybrid model is an extension for the SEIR model [ 63 ] that includes mobility tracing [ 64 ]. Fourth, the Institute for Health Metrics and Evaluation COVID-19 (IHME COVID-19) model also builds on the SEIR model to assess whether COVID-19 case rates would exceed the capacity of healthcare facilities [ 65 ].…”
Section: Methodsmentioning
confidence: 99%
“…Secondly, the deep transfer learning (DTL) model [ 61 ] focuses on real-time remote surveillance and monitoring of mask-wearing protocols at points of interest. Thirdly, the University of Virginia Biocomplexity Center PatchSim COVID-19 [ 62 ] hybrid model is an extension for the SEIR model [ 63 ] that includes mobility tracing [ 64 ]. Fourth, the Institute for Health Metrics and Evaluation COVID-19 (IHME COVID-19) model also builds on the SEIR model to assess whether COVID-19 case rates would exceed the capacity of healthcare facilities [ 65 ].…”
Section: Methodsmentioning
confidence: 99%
“…Another interesting study was carried out by Venkateswaran and Damani (2020) where they developed a customized system dynamics model for India to calibrate the effectiveness of several actions such as testing, tracing, social distancing, and hygiene in tackling COVID-19. Price and Propp (2020) developed a framework for assessing different late-stage models of COVID-19 through an extensive study conducted in Virginia where the study aimed at aiding policymakers through the developed system dynamics model to determine the plans to relax physical distancing by strategy.…”
Section: Related Work System Dynamicsmentioning
confidence: 99%
“…For evacuations conducted during the COVID-19 pandemic, additional risk of transmission is introduced via two main modes: (1) aggregation of large populations in community reception centers (in particular, large open shared spaces such as auditoriums and gymnasiums), and (2) community interaction of those that self-evacuate by car as they interact in gas stations, restaurants, and ultimately within the homes of family and friends. In preparation for the 2020 hurricane season, studies indicated that evacuations, both self-evacuation by car as well as structured evacuation to communal shelters, would result in a statistically significant increase in COVID-19 transmission in both the evacuated and receiving populations ( Pei et al 2020 ; Price et al 2020 ). The increase in transmission occurred even in the baseline scenario, where the origin and destination locations had the same rate of community transmission, and were even more pronounced when the destination location had a higher rate of community transmission.…”
Section: Introductionmentioning
confidence: 99%
“…Community spread associated with evacuations was estimated to result in tens of thousands of excess COVID infections and hundreds of excess fatalities from evacuees and could be a major source of infectious spread ( Pei et al 2020 ; Price et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%